Dissociation and Synesthesia: the Modalities of the Senses’ Presence in Theatre (Itinera, 2017)
In this article we propose an excursus of how spectators’ five senses are activated throughout different ages in representative or performative theater. We have opted to present our work divided into differing sections, each one corresponding to the sense which seemed to us to prevail. In this way we have noted that each theatrical performance proposes a sensory communication and a hierarchisation of the senses specific to it, in emphasizing dissociation, disjunction, alternation or synaesthesia.